PENGGUNAAN MEDIA KONKRET UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA POKOK BAHASAN GARIS BILANGAN PADA PESERTA DIDIK KELAS III MI DATOK SULAIMAN KOTA PALOPO - Sri Sulviani (Institut Agama Islam Negeri Palopo, 2019)
This research is a Classroom Action Research (CAR) which is the main problem of the low level of mathematics learning outcomes of class III students of MI Datok Sulaiman Palopo City. The research subjects were MI Datok Sulaiman third grade students in the odd semester of 2018/2019 school year with 28 students. This study was carried out in two cycles with number line material. Data collection techniques used consist of tests, observations, and documentation. Data processing and analysis techniques used are quantitative data analysis and qualitative analysis. The results showed that the learning outcomes with the number line material obtained by the average learning outcomes of students in cycle I was 64.85 including the category of not achieving the KKM score (Minimum Completeness Criteria) with the number of students completing learning were 11 people with a percentage of 39%, and learning outcomes in the second cycle on average obtained 82.89 including very good category with the number of students completing 26 with a percentage of 93%. This research was declared successful with the use of concrete media to improve mathematics learning outcomes.